A direct fragmentation method with Weibull function distribution of sizes based on finite- and discrete element simulations. (February 2016) - Paluszny, Adriana; Tang, XuHai; Nejati, Morteza; Zimmerman, Robert W.
Highlights: A direct method fragments bodies during discrete element method simulations. It applies patterns and size distributions from numerical and physical experiments. Weibull parameters approximate the fragment size distributions. Structured domain decomposition is applied on the colliding bodies directly. The method is mesh independent and does not increase refinement. Abstract: A direct method is proposed to rapidly fragment bodies during impulse-based discrete element method simulations of multiple body interactions. The approach makes use of patterns and size distributions obtained both from experiments, and from numerical models that rigorously compute fragmentation by growing fractures explicitly. Weibull parameters approximate the fragment size distributions as a function of body size and relative contact velocity. Structured domain decomposition is applied on the colliding bodies directly, resulting in a low-cost fragmentation calculation that depends on relative velocity, but which does not require the computation of fracture growth nor explicit element de-bonding, but instead classifies pre-existing mesh elements into the newly fragmented sub-domains. The method is applied to the fragmentation of a single spherical rock fragment, to an irregularly shaped rock fragment, and to the crushing of an array of spherical rock fragments.